2015
DOI: 10.1051/0004-6361/201527140
|View full text |Cite
|
Sign up to set email alerts
|

The eccentric short-period orbit of the supergiant fast X-ray transient HD 74194 (=LM Vel)

Abstract: Aims. We present the first orbital solution for the O-type supergiant star HD 74194, which is the optical counterpart of the supergiant fast X-ray transient IGR J08408-4503. Methods. We measured the radial velocities in the optical spectrum of HD 74194, and we determined the orbital solution for the first time. We also analysed the complex Hα profile. Results. HD 74194 is a binary system composed of an O-type supergiant and a compact object in a short-period (P = 9.5436 ± 0.0002 d) and high-eccentricity (e = 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 27 publications
1
24
1
Order By: Relevance
“…HD 74194 also known as LM Vel is supergiant system (Gamen et al 2015). This system is excluded from analysis.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…HD 74194 also known as LM Vel is supergiant system (Gamen et al 2015). This system is excluded from analysis.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…[23]), but nevertheless they can occur also at other orbital phases ( [24], [6]) and remarkably, in all sources but IGR J11215-5259, not every periastron passage triggers luminous flares. For example, after the recent determination of the orbital geometry in IGR J08408-4503 ( [23]), it is now evident that the long X-ray observation performed with Suzaku by [25] covered a large orbital phase interval just around periastron, and no bright flares were caught. However, it is important to remark that in a few SFXTs the orbital period has been discovered thanks to a periodic modulation in their long-term X-ray light curve (sometimes still present after removing bright flares).…”
Section: Pos(multif2017)052mentioning
confidence: 97%
“…Supergiant Fast X-ray Transients -A short review Lara Sidoli [27] 2.7 [28] 9.5436 [23] 0.63 [23] -285 ± 10 [23] IGR J11215-5952 B0.5Ia [29], [30], [31] >7 [31] 164.6 ,[32, 21, 33] >0.8 [31] 187 [34,15] -IGR J16328-4726 O8Iafpe [35], [36], [37] 7.2 [38] 10.068 [39], [40] ---IGR J16418-4532 OB Sg ∼13 [41] 3.753 [42] -1212 [43] 14.6842 [44], [45] IGR J16465-4507 O9.5Ia [46] 9.5 [47] 30.243 [48], [49] -228 [50] -IGR J16479-4514 O8.5I, O9.5Iab [51], [52] 4.9, 2.8 [51], [52] 3.3194 [53], [22] --11.880 [44], [45] XTE J1739-302…”
Section: Pos(multif2017)052mentioning
confidence: 99%
“…The results of our magnetic field measurements, those for the entire spectrum or only the hydrogen lines are presented in Table 1. The orbital phases of IGR J08408−4503 were calculated relative to a zero phase corresponding to the periastron passage at T per = 2454654.04 (Gamen et al 2015). The same zero phase as in the work of Lorenzo et al (2014) corresponding to the date of the first FEROS observation was adopted for IGR J11215−5952.…”
Section: Observations and Magnetic Field Measurementsmentioning
confidence: 99%
“…The optical counterpart of the system IGR J08408−4503 is the O-type supergiant star HD 74194 with spectral classification O8.6 Ib-II(f)p (Sota et al 2014). The orbital solution (P orb = 9.5436 ± 0.002 d, e = 0.63 ± 0.03) was for the first time determined by Gamen et al (2015). This work also indicated that the equivalent width of the Hα line is not modulated entirely with the orbital period, but seemed to vary with a superorbital period (P = 285 ± 10 d) nearly 30 times longer than the orbital one.…”
Section: Introductionmentioning
confidence: 96%